Teaching Science Communication with Comics for Postgraduate Students - Robin, Olivier; Leblanc, Benoît; Dumais, Nancy (Frontiers in Communication, 2021)
Data visualisation and visual storytelling are increasingly common terms when institutions and scientists want to introduce people to their research and science through stories. Yet institutions mostly teach and train their scientists in the language of science and scientific journals, whereas research dissemination calls for other forms of communication. A new university course introducing such a new form of communication is proposed to postgraduate students at Université de Sherbrooke since January 2020. Its main objective is to help students develop their general interest and skills into science communication using comics as a working medium. While following a simple path, this course has generally led to results beyond initial expectations and large engagement from students. This paper describes the general context and structure of the course, analyzes feedback from participants, presents some results and summarizes lessons learned to help the diffusion of such a cross-disciplinary course.